Assessment of the teaching of Islamic and Asian Civilisation (TITAS) with the use of Audio Visual Aids (AVA) - Talib, Ahmad Tarmizi; Gill, Sarjit S.; Fatmi Talib, Nor Hayati; Mohd Shafie, Bani Hidayat; Tamuri, Ab Halim; Kunasekaran, Puvaneswaran (Marsland Press, 2015)
The study to identify the first semester, Advanced Diploma students’ perceptions towards the teaching and learning of Islamic and Asian Civilisation (TITAS) with the use of Audio Visual Aids (AVA) in two polytechnics of Malaysia Higher Education Ministry (MOHE). Respondents are 33 students of Advanced Diploma Programme which are the overall population in the two polytechnics chosen for the study. The findings revealed that there is a high perception towards the teaching and learning of the course where the mean score of set induction as in 4.53 (SD 0.47), teaching and learning progress as in 4.48 (SD 0.39), approach as in 4.47 (SD 0.38), value inculcation as in 4.52 (SD 0.42), closure as in 4.32 (SD 0.56) and the use of audio visual aids (AVA) as in 4.32 (SD 0.39). There is no significant difference between both polytechnics for the assessed variables as revealed in the comparative analysis.